Romantic Partner Engagement in Muscle-Strengthening Physical Activity: A Qualitative Study. (January 2023) - Karakehayova, Magdalena; Smoliak, Olga; Milhausen, Robin
Physical activity is generally regarded as imperative to good health. Given the many health benefits of physical activity and the inclusion of muscle-strengthening physical activity (MSPA) in public health guidelines, an understanding of how romantic partners might foster or inhibit MSPA may be useful in promoting health and relationship quality. This study qualitatively explored how participants (young adults in long-term, dyadic heterosexual relationships) make sense of their partner's engagement in MSPA. The data came from the social media platform Reddit. The thematic analysis suggested five ways in which participants made meaning about MSPA in the context of their romantic relationships. Specifically, participants described experiencing conflict around partner engagement in MSPA, dissatisfaction with the partner's body, concern for partner's health, insecurity in response to physical changes in the partner, and concerns related to the partner balancing responsibilities and commitments. Limitations and implications of the analysis are discussed.